(untitled) (The International Journal of Educational Sciences and Arts, 2024)
AI applications were not limited to scientific questions, but were transformed into an information network applied in the visual arts, contributing in some way to the transition from the art support board to a data-driven visual world from the idea to the idea "Pixel" becoming a holistic creative art field, help the artist to follow the evolution and facilitate the artistic process, except in terms of knowledge or technical skills that the artist acquires through multiple experiences in his relationship with the past and present and looking to the future through the artist’s use of artificial intelligence in the artistic image that no longer awaits the eye of the artist, artistic experiences, scientific orientations and creative feelings. But this intelligence is impossible as an artist, thinking, collecting and extracting data in a result that is a simulation of a work of art. It is not a simple ordinary simulation of its constructive or colored composition but a synthesis of my information that produces an artistic image based on digital perception and robotics. Objectives: to determine the relationship of the artistic image with the concept of creativity, is the intelligent industrial image considered as a work of art orIs it based on creativity or is it just an intermediary between the machine and the work of art. Methods: The research program followed the analytical descriptive approach of the problems posed by the emerging controversial relationship between the concept of artificial intelligence and the image of art and the role of the artist in the developed innovative process, while describing the problem in question and collecting and analyzing the data surrounding it and extracting the results based on various proofs of the intellectual and aesthetic field of contemporary visual arts. Results: To highlight the role of AI technology in the development of the aesthetic and formative orientation of the artistic image. The study of the artist’s relationship with the art image through artificial intelligence and its place in this new digital field is the relationship of AI with the art image on the positive side and the negative side of its impact on the artist and the creative process. Define the limits of artificial intelligence in the production and creative value of the image, and guide creators in the fields of artistic image to highlight the role of artificial intelligence in the process of evolution in the visual arts. Conclusion: Study of the role of artificial intelligence technology in the development of the art image in contemporary art And that artificial intelligence in the arts considers the image or is a product based on artistic creativity and role of the artist in this huge surge of artificial technology that can eliminate his role and refer him to fringe and a practitioner and a simple technical rather than creative manufacturer in his field of research in contemporary methods of artistic creativity in art image.